Ben cao gang mu. Volume II, Waters, fires, soils, metals, jades, stones, minerals, salts : 16th century Chinese encyclopedia of materia medica and natural history - Li, Shizhen, 1518-1593; Unschuld, Paul U. (Paul Ulrich), 1943- (Oakland, California : University of California Press, 2021)
Volume II in the Ben cao gang mu series offers a complete translation of chapters 5 through 11, devoted to waters, fires, soils, metals, jades, stones, minerals, and salts. The Ben cao gang mu is a sixteenth-century Chinese encyclopedia of medical matter and natural history by Li Shizhen (1518-1593). The culmination of a sixteen-hundred-year history of Chinese medical and pharmaceutical literature, it is considered the most important and comprehensive book ever written in the history of Chinese medicine and remains an invaluable resource for researchers and practitioners. This nine-volume series reveals an almost two-millennia-long panorama of wide-ranging observations and sophisticated interpretations, ingenious manipulations, and practical applications of natural substances for the benefit of human health. Paul Unschuld's annotated translation of the Ben cao gang mu, presented here with the original Chinese text, opens a rare window into viewing the people and culture of China's past.
Description based on online resource; title from digital title page (viewed on February 28, 2022).
JSTOR
Keywords: Materia medica -- China -- Early works to 1800.; Medicine, Chinese -- Early works to 1800.; Natural history -- China -- Pre-Linnean works; Matière médicale -- Chine -- Ouvrages avant 1800.; Médecine chinoise -- Ouvrages avant 1800.; Sciences naturelles -- Chine -- Ouvrages prélinnéens.; MEDICAL / Acupuncture; Materia medica; Medicine, Chinese; Natural history; China; Early works